2003
DOI: 10.1007/s00415-003-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

A disease-specific psychosocial questionnaire for Parkinson?s disease caregivers

Abstract: The BELA-A-k is a relevant, reliable and valid measure for assessing psychosocial problems and need for help of PD-caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…The caregiving role by relatives of bipolar patients is very demanding, frequently distressing and harmful to health and quality of life [13]. Caring for a family member with Parkinson's disease is a long, stressful process that imposes heavy demands on emotional and physical resources and thus influences quality of life [14].…”
Section: Introductionmentioning
confidence: 99%
“…The caregiving role by relatives of bipolar patients is very demanding, frequently distressing and harmful to health and quality of life [13]. Caring for a family member with Parkinson's disease is a long, stressful process that imposes heavy demands on emotional and physical resources and thus influences quality of life [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some researchers create their own cut-off points, leading to inconsistencies and misleading conclusions. Some consider diseasespecific instruments more effective (Spliethoff-Kamminga et al, 2003) as they consider objective burden to vary between long term conditions (Bayen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…BELA-A-k is designed to measure psychosocial problems and need for help in people affected by PD (Spliethoff-Kamminga et al, 2003). It can be applied to both patients and carers and it is a part of PD diagnostic routine in Germany.…”
Section: Disease-specific Measuresmentioning
confidence: 99%
“…Parkinson’s caregivers have been recognized to play an important role in supporting patients, particularly in advanced stages of the disease leading a reduction of the rates of institutionalization and number of hospitalizations [10, 11]. However, caring for a family member with PD has been considered as a stressful process that affects negatively physical, psychological and socioeconomic conditions of caregivers [12]. It has been reported that caring a patients with PD is strongly related to poor psychosocial outcomes including high levels of burden, depression, anxiety, mood disturbances and emotional distress [13–15].…”
Section: Introductionmentioning
confidence: 99%
“…More recently several instruments such as the BELA-A-K [12] and the Scale of Quality of Life Care-Givers (SQLC) [22] have been specifically developed for caregivers of people with PD. Although these measures provide clinically important information of physical and psychological factors affecting to the role of caregivers, their feasibility has not formally been reported for English and Spanish speaking population [23].…”
Section: Introductionmentioning
confidence: 99%